Public administration in Libya: continuity and change - Sawani, Youssef Mohammad (2018)
Libyan public administration has been shaped by Libya$1 (Bs history, ideology, and economy. It has been negatively affected by the political changes occurring since independence in 1951, particularly Gaddaf$1 (Bs distinctive initiatives, and by upheavals in the post-Gaddafi transition. Libya$1 (Bs rentier economy has had its impact on public administration, particularly through its promotion of widespread public corruption. This article analyzes the history of Libya$1 (Bs politico-administration system before describing the current administrative arrangement, identifying the essential factors that have given rise to those arrangements, and analyzing the contemporary characteristics of public administration that constitute the key future challenges Libya faces. - Reproduced.s